2022
DOI: 10.1093/pasj/psac012
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of the molecular cloud, N4, in SS 433: Evidence for an interaction of molecular cloud with the jet from SS 433

Abstract: We conducted observations and analyses of the molecular cloud, N4, which is located at ∼40 pc from SS 433 and the same line of sight as that of the radio shell, in 12CO(J = 1–0), 12CO(J = 3–2), 13CO(J = 3–2), and grand-state OH emissions. N4 has a strong gradient of the integrated intensity of 12CO(J = 1–0, 3–2) emission at the northern, eastern, and western edges. The main body of N4 also has a velocity gradient of ∼0.16 km s−1 (20″)−1. A velocity shift by up to 3 km s−1 from the systemic velocity at ∼49 km s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…We have detected a new knot, w1.5, located between the previously known knots, w1 and w2 (figure 1). As shown in figure 6d, the location of the knot w1.5 coincides with the peak of the 12 CO emission, which is from the molecular cloud, N4 (Yamamoto et al 2008;Su et al 2018;Yamamoto et al 2022). The figure also shows that 12 CO emission has a clear positive correlation with X-ray absorption column densities.…”
Section: Origin Of Knotssupporting
confidence: 53%
See 3 more Smart Citations
“…We have detected a new knot, w1.5, located between the previously known knots, w1 and w2 (figure 1). As shown in figure 6d, the location of the knot w1.5 coincides with the peak of the 12 CO emission, which is from the molecular cloud, N4 (Yamamoto et al 2008;Su et al 2018;Yamamoto et al 2022). The figure also shows that 12 CO emission has a clear positive correlation with X-ray absorption column densities.…”
Section: Origin Of Knotssupporting
confidence: 53%
“…The figure also shows that 12 CO emission has a clear positive correlation with X-ray absorption column densities. Yamamoto et al (2022) reported that the temperature of this cloud is higher than that of typical clouds in the Galactic plane, and a velocity shift of up to 3 km s −1 from the velocity of the entire cloud (∼ 49 km s −1 ) was detected only in the northwestern part. These results suggest that most of the cloud is located in front of the jet, and a part of the cloud is interacting with the jet.…”
Section: Origin Of Knotsmentioning
confidence: 78%
See 2 more Smart Citations
“…The western-side clouds (N1-N4) are closer to SS 433, and Liu et al (2020) observed N1, N2, and N3 with higher spatial resolution and concluded that a part of them is located within W50. Recently, Yamamoto et al (2022) reported the observation of N4. The molecular cloud has an asymmetric spectrum for CO emission and an extreme temperature gradient.…”
Section: Introductionmentioning
confidence: 99%